2022
DOI: 10.3390/pr10020307
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Degradation by a Novel Strain Pseudomonas aeruginosa AQNU-1 Isolated from an Oil-Contaminated Lake Wetland

Abstract: In this study, a novel crude oil degrading bacterium was isolated from an oil-contaminated freshwater lake using crude oil as the sole carbon source. The strain was named Pseudomonas aeruginosa AQNU-1 based on the analyses of its morphological characteristics and 16S rRNA gene sequencing. Gas chromatography-mass spectrometry (GC-MS) was carried out to investigate the degradation of crude oil fractions under dynamic (37 °C, 180 r/min) and static (37 °C, 0 r/min) cultivation over three months of continuous enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Additionally, in the current experiment indicate the presence of various functional groups and bond strengths in the samples subjected to analysis, another study reported that the diesel oil act as a medium distillate of petroleum possessing different proportions of branched alkanes, nalkanes, olefins with low concentration of aromatic polycyclic components (13,33). According to the analysis, the absence of characteristic peaks in the region of 1610-2042 in extracted samples indicated absence of nitro compound linkage.…”
Section: Fourier Transform Infrared [Ftir] Analysissupporting
confidence: 53%
“…Additionally, in the current experiment indicate the presence of various functional groups and bond strengths in the samples subjected to analysis, another study reported that the diesel oil act as a medium distillate of petroleum possessing different proportions of branched alkanes, nalkanes, olefins with low concentration of aromatic polycyclic components (13,33). According to the analysis, the absence of characteristic peaks in the region of 1610-2042 in extracted samples indicated absence of nitro compound linkage.…”
Section: Fourier Transform Infrared [Ftir] Analysissupporting
confidence: 53%
“…Pseudomonas is one of the well-known hydrocarbon degraders using the terminal oxidation pathway [31]. Recently, a member of this genus, P. aeruginosa, was isolated from an oil-contaminated lake wetland and reported to degrade up to 100% of C13-C35 hydrocarbons in crude oil [32]. In another work, this species was reported to degrade n-alkanes and polycyclic aromatic hydrocarbons at efficiencies of 80% and 98%, respectively [31].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas sp. has been observed as a main oil hydrocarbon responder in fresh water from lake wetlands [ 55 ] and rivers [ 56 ]. At day 7, the relative abundance of these genera slightly decreases and they are outperformed by Aquabacterium , which is the most abundant genus.…”
Section: Discussionmentioning
confidence: 99%